A systematic review and meta-analysis of interventions incorporating behaviour change techniques to promote breastfeeding among postpartum women. Issue 3 (3rd July 2019) - Kassianos, Angelos P.; Ward, Emma; Rojas-Garcia, Antonio; Kurti, Allison; Mitchell, Fiona C.; Nostikasari, Dian; Payton, Jamie; Pascal-Saadi, Julian; Spears, Claire Adams; Notley, Caitlin
ABSTRACT: The benefits of exclusive breastfeeding are well documented, yet few women adhere to recommendations. We report the Behaviour Change Techniques (BCTs) within interventions trialled internationally after pregnancy to promote exclusive and mixed breastfeeding as well as evidence of effectiveness. PsycINFO, EMBASE and MEDLINE databases were screened. Twenty-three ( n  = 23) studies met inclusion criteria. Three authors independently extracted data, coded interventions using the BCT v.1 taxonomy, and assessed study quality. There was a moderate significant effect of the interventions promoting exclusive breastfeeding up to four weeks postpartum (OR 1.77, [95% CI: 1.47–2.13]) but this effect slightly declined beyond thirteen weeks (OR 1.63, [95% CI: 1.07–2.47]). Twenty-nine BCTs were identified within interventions. 'Credible source' and 'instruction on how to perform the behaviour' were the most prevalent and 'social support (unspecified)' contributed to the effectiveness of exclusive breastfeeding interventions five to eight weeks postpartum. Using BCTs with cognitive and behavioural aspects may help women develop coping mechanisms promoting exclusive breastfeeding. Further trials are needed in countries with low breastfeeding rates such as the UK. The use of programme theory during intervention development and clear description of intervention components is recommended. This meta-analysis provides guidance for trials evaluating postpartum breastfeeding interventions.